Penegakan Hukum terhadap Tindak Pidana di Bidang Pengukuran - Titie Yustisia Lestari; Ridwan Tahir; Andi Afdhalia Sri Hayati (Universitas Batanghari Jambi, 2019)
In trade traffic and buying and selling transactions, measuring instruments, measurements, and scales are one of the most vital and necessary facilities in supporting the realization of a transaction of goods and services. Its purpose is to determine the unit and weight of the goods and services which are the object of the trade and the transaction. For that reason, in every trade transaction, especially trade in goods, measurement tools, measurements and scales that meet legal metrology standards are needed. or legal metrology or legale metrology. This means that the measurement tools, measurements, and scales used in each transaction must have the legality and validity of the agency that is authorized to do so, namely from the Legal Metrology or Metrology Technical Implementation Unit (UPT) which carries out the metrological tasks residing in Provincial and Regency / City level. This research is an empirical study conducted in the city of Palu using the interview and questionnaire method. The results showed that there were still many violations committed by Legal Metrology starting from the need to guarantee fairness in trade, especially in the area of measurement and weighing. Legal metrology is mainly concerned with measurement tools regulated by law. Irregularities in legal metrology among traders often occur due to lack of legal awareness and ignorance of the laws governing legal metrology. Factors inhibiting law enforcement against legal metrology criminal acts include a lack of public awareness about the law itself and a lack of socialization about threats criminal offenses against legal metrology abuse.